The Role of the Vestibular System in Balance Disorders and Falls in the Elderly: A Prospective Cohort Study with Posturography Assessment in Surabaya, Indonesia - Venny Melinda; Johan Wirahadi Putro; Mariana Alifah; Michelle Birne; Abhimanyu Putra (Sriwijaya Journal of Neurology, 2024)
Introduction: Falls in the elderly represent a significant public health concern, often leading to injury, disability, and reduced quality of life. The vestibular system plays a crucial role in maintaining balance, and its decline with age is a major contributor to falls. This study aimed to investigate the relationship between vestibular function, assessed through posturography, and the incidence of falls in elderly individuals in Surabaya, Indonesia. Methods: A prospective cohort study was conducted involving 150 participants aged 60 years and above residing in Surabaya. Baseline assessments included a comprehensive geriatric assessment, vestibular function tests using computerized dynamic posturography (CDP), and questionnaires on falls history. Participants were followed up for 12 months to record the occurrence of falls. Data analysis included descriptive statistics, correlation analysis, and logistic regression to identify predictors of falls. Results: The incidence of falls during the 12-month follow-up period was 32%. CDP revealed significant age-related decline in vestibular function, particularly in measures of sensory organization and balance strategy. Poor performance on CDP, especially in conditions with altered visual and proprioceptive inputs, was significantly associated with an increased risk of falls. History of previous falls, presence of comorbidities, and use of polypharmacy were also identified as significant predictors of falls. Conclusion: Vestibular dysfunction, as assessed by CDP, is a significant risk factor for falls in the elderly. Incorporating posturography assessment into routine geriatric evaluations may help identify individuals at high risk of falls, allowing for targeted interventions to prevent falls and associated complications.